PATHOMORPHOLOGICAL DYNAMIC DUST CHANGES OF LUNG VESSELS IN KUZBASS MINERS WITH DIFFERENT WORK EXPERIENCE - Бондарев, Олег Иванович; Сурков, Арнольд Михайлович; Азаров, Павел Алексеевич; Филимонов, Сергей Николаевич (Medicine in Kuzbass, 2023)
The professional activity of working in the mine for coal industry workers is marked by damage to the arteries, veins of the lungs with the involvement of all morphological elements of the vascular wall. Hypertrophy of the muscular layer of blood vessels, perivascular fibrosis and endothelial dysfunction cause tissue and cellular changes in the vascular system of the lungs with the development of pulmonary hypertension and can serve as a marker of the pneumoconiotic (PC) process. Organic changes in the vascular wall of the small circulatory circle when exposed to dust in miners in a single pathogenetic mechanism are not considered today as a manifestation of professionally conditioned pathology. Although there is an opinion about the significant effect of products from the cytotoxic effect of silicate dust and industrial poisons on the endothelium with the development of perivascular sclerosis [1, 2]. However, in the works on vascular pathology in PC in miners, there were no data from a pathomorphological study. The purpose of the study – to identify dynamic changes in the vascular system of the lungs depending on the length of exposure to coal-rock dust in workers of the main professions of the Kuzbass coal industry. Material and methods. We conducted a study of forensic histological and morphometric study of 50 forensic medical examinations of a group of miners (GS) who died simultaneously while working in a mine during a man–made disaster. According to the Rospotrebnadzor of Novokuznetsk, the level of dustiness of miners’ workplaces with coal-rock dust exceeds the maximum permissible concentrations up to several tens, and sometimes hundreds of times, i.e. it belonged to the hazard class of 1-4 degrees (class 3.1-3.4) [3]. The Control Group (GC) was formed from 30 cases of forensic medical examinations of Novokuznetsk men who died in road accidents, who were aged 25 to 55 years and had no visible organ pathology according to the results of autopsies (statistical group ICD Z 03). The object of the study was the histological and morphometric characteristics of the arteries and veins of the small circulatory circle (MCC, BCC available for light microscopy, as well as interstitial correlations of vascular structures). Statistical data processing was carried out using IBM SPSS Statistics 22 software (license agreement No. 20/604/3-1 dated 04/22/2016). The critical value of the significance level of differences is p = 0.05. Results of the study. Changes in the vessels of various veteran groups of miners were characterized by hypertrophy of smooth muscle tissue, sclerotic changes in the walls of arteries of various generations, as well as outside the vessels (perivascular spaces). In the perivascular zones of the miners’ groups, pronounced fibrosis of various volumes was noted, with massive inclusions of dust particles characterizing only GS. Fibroplastic changes were progressive in nature from the minimum length of service to pronounced changes in the group of 20 years. Conclusions. Endotheliosis, hypertrophy of smooth muscle cells and perivascular sclerosis of the arteries of the small circulatory circle are among the initial and progressive pathomorphological manifestations of the coniotic process in workers in conditions of increased dustiness, depending on the length of service. The morphological transition of the functional stage of hypertension in the hemodynamic system of the body to the organic one begins with the development of hypertrophy and proliferation of smooth muscle cells (MMC) of the vascular wall. The simultaneous development of pathological processes in the vessels of the lungs in PC characterizes the coniotic process as a general pathological problem of interstitial and intercellular interactions in the body.